Pilot Study on Feasibility of Sensory-Enhanced Rehabilitation in Canine Spinal Cord Injury - Lewis, Melissa J.; Bowditch, Jessica; Laflen, Brittany; Perry, Nicole; Yoquelet, Rachel; Thomovsky, Stephanie A. (Frontiers in Veterinary Science, 2022)
Physical rehabilitation is frequently recommended in dogs recovering from acute thoracolumbar intervertebral disc extrusion (TL-IVDE), but protocols vary widely. The objective of this study was to evaluate the feasibility of incorporating sensory-integrated neurorehabilitation strategies into a post-operative rehabilitation protocol in dogs with TL-IVDE. Non-ambulatory dogs with acute TL-IVDE managed surgically were prospectively recruited to this unblinded cross-over feasibility study. Eligible dogs were randomized to start with tactile-enhanced (artificial grass) or auditory-enhanced (floor piano) basic rehabilitation exercises performed twice daily for the first 4 weeks before switching to the opposite surface for the subsequent 4 weeks. Neurologic examination, open field gait scoring, girth measurements and an owner-completed feasibility questionnaire were performed at baseline and 2, 4, 6, and 8 weeks post-operatively. Twenty-four dogs were enrolled, 12 randomized to each order of exercises. Gait scores did not differ between the two groups at baseline, 4 or 8 week visits. All modified exercises could be performed and compliance was high. Adverse events potentially attributable to the study surface were mild, self-limiting and occurred in 2/24 dogs. The most common surface-related limitations were that the piano was slippery and that both surfaces were too short. The artificial grass was preferred by owners and dogs compared to the floor piano surface, but this was influenced by which surface was utilized first. Auditory and tactile modifications were feasible and safe to incorporate into a standardized rehabilitation protocol. This pilot study could prompt larger efficacy studies investigating the benefit of sensory-integrated rehabilitation in dogs with TL-IVDE.